Escape behaviour of Steamer Ducks - Livezey, Bradley C; Humphrey, Philip S (Wildfowl, 1982)
This paper presents results of field work during December-February 1980-81 at three sites in Argentina on the escape behaviour of White-headed Flightless Steamer Ducks Tachyeres leucocephalus, Flying Steamer Ducks T. patachonicus, and Magellanic Flightless Steamer Ducks T. pteneres. The three species studied differed in use of escape modes, not including flight. T. leucocephalus differed substantially from the generally more similar T. ptereres and T. patachonicus in frequency of escape modes, diversity of escape behaviour, and two-act behavioural sequences. Escape behaviour of pursued T. leucocephalus and T. patachonicus were affected by flock size and gunfire. We speculate that escape diving is used primarily to elude aerial predators (especially by ducklings) and that steaming functions as a target-obscuring method for escape from underwater predators.